Odpowiedzi

2009-10-19T00:25:12+02:00
9x - 3y = 6
6x + y = -2 /*3

9x - 3y = 6
18x+3y=-6
------------
27x=0/;27
x=0
tu będzie chyba układ oznaczony ..

2x + 5y = 5 /*(-3)
6x + 15 = 15

-6x-15y=-15
6x+15y=15
-------------
0x + 0y=0
układ nieoznaczony

-6x + 4y=8
-3x + 2y =-2 /*(-2)

-6x + 4y=8
6x-4y=4
-----------
0x+0y=12
układ sprzeczny


4x - 2y= 7 /*2
3x + 4y = 8

8x-4y=14
3x+4y=8
----------
11x=22 / :11
x=2
układ oznaczony



2x - y=0 / *(-2)
4x + 3 = y

-4x+2y=0
4x-y=-3
-----------
y=-3

2x-(-3)=0
y=-3

x=-3/2 ( /-jako kreska ułamkowa)
y=-3

układ oznaczony

1 4 1
2009-10-19T00:45:09+02:00
3x + y = 3
-x + 2y = -8
y = -3x +3
-x + 2*(-3x + 3) = -8
y = -3x +3
-x + (-6x) + 6 = -8
y = -3x +3
-7x = -8 - 6
y = -3x +3
-7x = -14 /-7
y = -3x +3
x = 2
y = -3 * 2 +3
x = 2
y = -6 + 3
x = 2
y = -3
sprawdzenie:
3 * 2 + (-3) = 6 - 3 = 3
-2 + 2 * (-3) = -2 + (-6) = -8
układ oznaczony

9x - 3y = 6
6x + y = -2
9x - 3y = 6
y = -6x -2
9x - 3 * (-6x - 2) = 6
y = -6x -2
9x + 18x + 6 = 6
y = -6x -2
27x = 6 - 6
y = -6x -2
27x = 0 /27
y = -6x -2
x = 0
y = -6 * 0 - 2
x = 0
y = -2
sprawdzenie:
9 * 0 - 3 * (-2) = 0 + 6 = 6
6 * 0 + (-2) = 0 - 2 = -2
układ oznaczony

2x + 5y = 5 / *(-3)
6x + 15y = 15
-6x - 15y = -15
6x + 15y = 15
-6x + 6x - 15y + 15y = -15 + 15
0 = 0
układ nieoznaczony

-6x + 4y = 8 / (-2)
-3x + 2y = -2
3x - 2y = -4
-3x + 2y = -2
3x - 3x - 2y + 2y = -4 - 2
0 = -8
układ sprzeczny

4x - 2y = 7
3x + 4y = 8 / 2
4x - 2y = 7
(3/2)x + 2y = 4
4x + (3/2)x - 2y + 2y = 7 + 4
(11/2)x = 11 / *2
11x = 22 / 11
x = 2
4 * 2 - 2y = 7
x = 2
8 - 2y = 7
x = 2
-2y = 7 - 8
x = 2
-2y = -1 / (-2)
x = 2
y = 1/2
sprawdzenie:
4 * 2 - 2 * (1/2) = 8 - 1 = 7
3 * 2 + 4 * (1/2) = 6 + 2 = 8
układ oznaczony

2x - y = 0
4x + 3 = y
2x - y = 0
y = 4x + 3
2x - (4x + 3) = 0
y = 4x + 3
2x - 4x - 3 = 0
y = 4x + 3
-2x - 3 = 0
y = 4x + 3
-2x = -3 / (-2)
y = 4x + 3
x = 3/2
y = 4 * (3/2) + 3
x = 3/2
y = 6 + 3
x = 3/2
y = 9
sprwadzenie:
2 * (3/2) - 9 = 3 - 9 = -6 (a nie 0)
4 * (3/2) + 3 = 9
układ sprzeczny
1 5 1